PENGEMBANGAN BAHAN AJAR MEMBACA KRITIS BERBASIS INTERVENSI RESPONSIF - Endah Tri Priyatni (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to: (1) develop a critical reading activity program integrated into a responsive intervention program in a multimedia package to improve the critical reading skill of undergraduate students of the department/study program of the Indonesian language and literature, and (2) investigate the effectiveness of the product to improve their critical reading skill. The study employed a research and development model adapted from the model of Recursive, Reflective Design and Development (R2D2). The development produced a critical reading program integrated into a responsive intervention program in a multimedia package. The results of the effectiveness test showed that the use of responsive-intervention-based critical reading learning materials with multimedia was capable of improving students’ critical reading skill.